2011
DOI: 10.1186/1743-422x-8-358
|View full text |Cite
|
Sign up to set email alerts
|

The heterogeneous ribonuclear protein C interacts with the hepatitis delta virus small antigen

Abstract: BackgroundHepatitis delta virus (HDV) is considered to be a satellite virus of the Hepatitis B virus. The genome consists of a 1679 nt ssRNA molecule in which a single ORF was identified. This ORF codes for a unique protein, the Delta antigen (HDAg). During transcription, two forms, small (S-HDAg; p24) and large (L-HDAg; p27) of this antigen are derived as a result of an editing mechanism catalyzed by cellular adenosine deaminase 1. Despite its simplicity, little is still known about the host factors that inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…This set included 9 of the 12 subunits of the pol II complex, further supporting the idea that pol II is involved in HDV RNA transcription [106]. In another study, a yeast two-hybrid approach identified 30 proteins encoded by a human liver cDNA library that interacted with S-HDAg [107]. Only three proteins from this study had also been identified by the previously mentioned immunopurification approach.…”
Section: Delta Antigenssupporting
confidence: 66%
“…This set included 9 of the 12 subunits of the pol II complex, further supporting the idea that pol II is involved in HDV RNA transcription [106]. In another study, a yeast two-hybrid approach identified 30 proteins encoded by a human liver cDNA library that interacted with S-HDAg [107]. Only three proteins from this study had also been identified by the previously mentioned immunopurification approach.…”
Section: Delta Antigenssupporting
confidence: 66%
“…The HDV genome consists of approx. 1680 nucleotides covered by approximately 200 hepatitis D antigen molecules (HDAg) [ 2 , 9 ]. HDV needs the presence of HBV envelope proteins for its assembly, propagation, and transmission to initiate new rounds of infection [ 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a high expression of HNRNPC has a poor prognosis and may act as a candidate biomarker for chemoresistance in gastric cancer ( Huang et al, 2016 ). Besides that, HNRNPC also acts as a dengue virus NS1-interacting protein and plays an important role during the replication of the hepatitis C virus and hepatitis delta virus ( Noisakran et al, 2008 ; Casaca et al, 2011 ). Our results imply that HNRNPC is a candidate biomarker for HCC.…”
Section: Discussionmentioning
confidence: 99%